2015
DOI: 10.1210/jc.2015-1841
|View full text |Cite
|
Sign up to set email alerts
|

DDT Exposure in Utero and Breast Cancer

Abstract: This prospective human study links measured DDT exposure in utero to risk of breast cancer. Experimental studies are essential to confirm results and discover causal mechanisms. Findings support classification of DDT as an endocrine disruptor, a predictor of breast cancer, and a marker of high risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
148
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(159 citation statements)
references
References 49 publications
2
148
1
3
Order By: Relevance
“…In preliminary studies by our group and other groups, the environmental pollutants polychlorinated biphenyls (PCBs) have demonstrated a propensity to disturb systemic iron homeostasis through estrogenic effects, increasing breast cancer risk 40, 41, 42. A recent study by Cohn et al suggested that dichlorodiphenyltrichloroethane (DDT) exposure during pregnancy leads to increased risk of breast cancer later in life 43. BPA, one of the most ubiquitous and thoroughly studied EDCs, is also weakly estrogenic and there has been concern regarding the role BPA may play in the development of breast cancer over years 44, 45, 46.…”
Section: Introductionmentioning
confidence: 99%
“…In preliminary studies by our group and other groups, the environmental pollutants polychlorinated biphenyls (PCBs) have demonstrated a propensity to disturb systemic iron homeostasis through estrogenic effects, increasing breast cancer risk 40, 41, 42. A recent study by Cohn et al suggested that dichlorodiphenyltrichloroethane (DDT) exposure during pregnancy leads to increased risk of breast cancer later in life 43. BPA, one of the most ubiquitous and thoroughly studied EDCs, is also weakly estrogenic and there has been concern regarding the role BPA may play in the development of breast cancer over years 44, 45, 46.…”
Section: Introductionmentioning
confidence: 99%
“…The strongest relationship was seen in women who were <14 years in 1945 [odds ratio (OR) = 5.4, 95% CI 1.7-17.1]. This study, which cannot be replicated because of the unusual nature of the data set, supports the concept that the timing of exposure (i.e., early development window) may be critical to the contribution of EDCs to carcinogenesis (23). Supportive evidence comes from the Sister Study, which found that young girls up to age 18 years who were exposed to fogger truck or plane spraying of DDT were at a nonsignificant increased risk of breast cancer [hazard ratio (HR) = 1.3, 95% CI: 0.92-1.7] for premenopausal breast cancer (100).…”
Section: Pesticidesmentioning
confidence: 71%
“…These data are drawn from cancer registries covering a sample of the general population that is representative in sex, race, and age. 2 The increase in incidence is remarkably similar among infants (ages 0-4) and among teenagers (ages [15][16][17][18][19], whereas the rates in the middle years are lower and rising only slightly. Siegel et al 3 recently reported that the overall cancer incidence rate in the years 2001 to 2009 was rising among African American children more rapidly than among white children.…”
mentioning
confidence: 99%
“…There are important but still limited data demonstrating that exposures to chemical carcinogens and radiation during the critical developmental periods of gestation, childhood, and adolescence can lead to cancers much later in life. 8,14,15 The underlying causal web for exposures in childhood that lead to cancer later in life is undoubtedly complex, and we may never arrive at a definitive understanding of all the causes and their relative importance. But in our view, the unexplained and striking increases in childhood cancer incidence rates ( Fig 1) and the steady increases in some adult cancers with strong links to chemical exposures such as non-Hodgkin lymphoma and kidney cancer, noted earlier, justify a call to take steps now to prevent carcinogen exposures, beginning in childhood.…”
mentioning
confidence: 99%